How gamification affects online shopping behavior: An approach with youngsters (aged 16 – 30) - Dinh Tien Minh; Le Vu Lan Oanh; Nguyen Diem Quynh (Cogent Business & Management, 2023)
Online shopping has grown in popularity over the past few years, particularly in the context of COVID-19. Gamification is also progressively emerging as an ideal means to boost motivation and encourage community engagement. This study attempts to identify the variables influencing young Vietnamese people's willingness to adopt gamification and its impact on their buying habits in order to suggest practical solutions for business marketing initiatives. The study uses a quantitative research approach with simple random sampling (n = 230). The number of valid samples officially included in the study is 288 as a consequence of the survey results. The results suggest that the following elements significantly impact the intention to adopt gamification: favorable circumstances, effort expectations, social influence, and performance expectations. These have a 54.1 percent impact on gamification acceptance intent and a 29.6 percent impact on online shopping behavior. Finally, the study's findings are used to make various suggestions to improve gamification's effectiveness in marketing activities.
Keywords: 650; customer behavior; e-marketing; gamification; online shopping behavior